Study of martensite in hydraulically pressed 60C2A steel by internal friction method - Aleksandrov, N.G.; Petchenko, A.M.; Rokhmanov, N.Ya. (Functional Materials, 2004)
Thin structure changes in martensitic state of 60C2A steel have been studied using acoustic spectroscopy, optical microscopy and X-ray one. The hydraulic pressing followed by aging and quenching of the specimens has been found to influence considerably the level and temperature localization of the internal friction as well as the relaxation stab ility parameters, coercive force, and microhardness. This fact is associated with carbon depos i-tion from the solid solution and distortion of tetragonal character thereof. Методами акустической спектроскопии, оптической и рентгеновской микроскопии исследованы тонкие структурные изменения мартенситного состояния термообработанной стали 60C2A. Установлено, что гидропрессование с последующим старением и закалкой образцов существенно влияет на уровень и температурную локализацию внутреннего трения, а также на параметры релаксационной стойкости, коэрцитивную силу и микротвердость, что связывается с выделением углерода из твердого раствора и снижением тетрагональности его решетки. Методами акустичної спектроскопії, оптичної i рєнтгєнівської мікроскопії досліджено тонкі структурні зміни мартенситного стану термообробленої сталі 60C2A. Встановлено, що гідропресування з наступним старінням та загартовуванням зразків суттєво впливає на рівень і температурну локалізацію внутрішнього тертя, а також на параметри релаксаційної стійкості, коерцітивну силу та мікротвердість, що пов’язується з виділенням вуглецю із твердого розчину та зниженням тетрагональності його гратки.